BENTUK PENYAJIAN MUSIK IRINGAN TARI TOTOKNG PADI PADA ACARA NAIK DANGO KECAMATAN SAMALANTAN BENGKAYANG - Batubara, Herlina Merdekawati; Ismunandar, Ismunandar; Silaban, Christianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research analyzed the form of Totokng Padi Dance Musical Accompaniment Performance on Samalantan Sub-district in Bengkayang Regency. The problem of this research were (1) How was the form of Totokng Padi Dance Musical Accompaniment Performance in Naik Dango Event on Samalantan Sub-district in Bengkayang Regency (2) How was the contribution of Totokng Padi Dance Musical Accompaniment Performance as the teaching material in teaching learning process at school. Descriptive metho in qualitative research with ethnomusicology approach was done to execute this research. The source of the data were Titus Jaman, Markus, and Sumiati. The data in this research were obtained through the interview and observation result in the form of voice records, photos, and videos about Totokng Padi. The technique in collecting the data were observation, interview, and documentation techniques. Moreover, to test the validity of the data, the research used Triangulation (Triangulation Resources) The result of the research were music instument, player, stage arrangement, makeup, fashion, sound arrangement, lighting arrangement, formation, and the order of performance. These results were expected to be a contribution to the teaching material about Totokng Padi, to comprehend about the Totokng Padi Musical Accompaniment, uniqueness of Totokng Padi and exhibition (?) for grade 10 of first Semester in 2013 Curriculum. Keywords: the form of the performance, Musical Accompaniment, Totokng Padi, Samalantan Sub-district.